Temperature Effects on Phosphorus Release from a Biosolids-Amended Soil - Maria L. Silveira; George A. O'Connor (Applied and Environmental Soil Science)
This study was designed to evaluate the effects of temperature on the potential leachable P pool and distribution of chemical P forms in a biosolids-amended soil. A P-deficient Spodosol was incubated with seven biosolids and inorganic P fertilizer at 20 and 32°C for 90 days. Amendments were applied to provide a total P concentration of 112 mg kg−1 soil, which correspond to a field application of ~224 kg P ha−1. Cumulative P mass leached during the 90 d study for any P source was <2% of the applied P, but greater cumulative P mass was released from the biological P removal and composted biosolids than from the heat-dried materials. Increasing temperature (20 to 32°C) generally decreased cumulative P mass leached, suggesting greater soil affinity to retain P at 32°C than at 20°C. In a static incubation experiment (no leaching), soil water-extractable P concentrations were reduced over time, but no temperature effect was observed. Similarly, P distribution among the various fractions was not affected by temperature. The relatively great ability of the soil to sorb P masked differences in biosolids properties and the potential impacts of temperature on P lability. Additional work using low P-sorbing soils is warranted.